2022
DOI: 10.3390/antiox11020234
|View full text |Cite
|
Sign up to set email alerts
|

Hydrangea macrophylla and Thunberginol C Attenuate Stress-Induced Anxiety in Mice

Abstract: Stress is an important neurological input for successful life. However, chronic stress and stress hormones could be a cause of various neurological disorders including anxiety disorders. Therefore, there have been many efforts to find effective materials for curing stress-induced neurological disorders. In this study, we examined the effect of Hydrangea macrophylla (HM) on corticosterone-induced neurotoxicity, stress-induced anxiety in mice and suggested a possible active ingredient of HM. HM protected cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Lee et al demonstrated that Hydrangea macrophylla and its active compound, thunberginol C, improved chronic restraint stress or corticosterone-induced anxiety behavior activity in mice [16]. These extracts also inhibited corticosterone and tumor necrosis factor-α levels in the blood.…”
mentioning
confidence: 99%
“…Lee et al demonstrated that Hydrangea macrophylla and its active compound, thunberginol C, improved chronic restraint stress or corticosterone-induced anxiety behavior activity in mice [16]. These extracts also inhibited corticosterone and tumor necrosis factor-α levels in the blood.…”
mentioning
confidence: 99%